Efektivitas Metode Experiential Learning dalam Meningkatkan Pengetahuan dan Efikasi Diri Kesehatan Mental pada Siswa SMA di Kota Balikpapan - Feriyanti, Alma; Permana, Lies; Agustini, Rina Tri; Nurrachmawati, Annisa; Rohmah, Nur; Rahayu, Agustin Putri; Fikri, Mohammad (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2025)
Background. Mental health disorders have become a significant global concern, with the Global Health Data Exchange reporting approximately 970 million individuals worldwide—equivalent to one in eight people—suffering from mental health issues, primarily depression and anxiety. Adolescents are particularly vulnerable due to academic and non-academic pressures. Experiential learning, an active educational approach, may serve as an effective method to enhance adolescent knowledge and self-efficacy regarding mental health. Objective. To analyze the effectiveness of the experiential learning method in improving adolescents’ knowledge and self-efficacy related to mental health. Method. This study employed a pre-experimental one group pretest-posttest design, conducted at a senior high school in Balikpapan City. A total of 30 students were selected purposively from a population of 444. Knowledge data were analyzed using the Wilcoxon Signed Rank Test, while self-efficacy data were analyzed using the paired t-test. Results. The N-Gain score was 0.65, indicating that the experiential learning method was moderately effective in improving students' knowledge and self-efficacy. Conclusion. Experiential learning is effective in enhancing adolescent understanding and confidence in managing mental health issues. This method is recommended as an interactive educational strategy and could be extended to other health topics to promote youth well-being.